A survey on MANET protocols in wireless sensor networks - Cynthia, Prudhvi Krishna Saguturu, C; Bandi, Komali; Magulluri, Srikanth; Anusha, T (International Journal of Engineering and Technology, 2018)
In Wireless sensor networks and ad hoc networks nodes have a freedom to move from one place to another, they are self-configuring this type of the structure fulfil the requirements of several application. A survey on the different MANET protocols will be done in this paper. Mainly this paper will focus on the Quality of Service on the different parameters like Throughput and Delay between different protocols like AODV (Ad Hoc on Demand Distance Vector), DSDV (Destination-Sequenced Distance-Vector Routing), DSR (Dynamic Source Routing), and TORA (Temporary Ordered Routing Algorithm). DSDV is called as proactive protocol because they know everything about the nodes in the network before the communication start. DSR, AODV, TORA protocols are called reactive protocol because nodes in this network do not know anything about network. They are also called ON-DEMAND routing protocols. After this analysis you will come to know which MANET protocol is best for different application.Â